Análisis del software Quantum Gis y su implementación en el sector productivo - Guzman Zabala, Juan Francisco
This article corresponds to a descriptive investigation of the Quantum Gis program for the training processes carried out within the Scepter of Technologies for Construction and Wood (CTCM) in the geomatics classroom, in turn that the trainees can identify the tools and main features of the program with the objective of using these training processes as an alternative of innovation and potential in the conventional topography in civil works, construction and above all, provide solutions to engineering and infrastructure problems in this way the main functions were identified as well. How the information is verified regarding its use within the productive sector in order to observe the benefits that the program offers us compared to conventional topography. Mainly it was found that the program has add-ons that facilitate data processing for any type of project, geographic information systems (GIS) such as topography, construction and multi-purpose cadastre among others. This tool has a great advantage and it can be developed for a processing need with specific characteristics.